Penerapan Metode Promethee pada Sistem Pendukung Keputusan Penerimaan Beasiswa - Nikomedes Oba Rendu; Kristina Sara; Anastasia Mude (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
A decision support system is a computer-based system that helps users in the decision-making process. In this study, the authors use the promethee method in the decision support system for receiving scholarships at the Information Systems Study Program, University of Flores. The Flores University Foundation Scholarship is a form of appreciation for the Foundation in helping potential students in the form of finances given in the current semester. This research was conducted by building outranking relations through pairwise comparisons by looking for the values ​​of entering flow, leaving flow and net flow. The stages in the promethee method consist of two main parts, namely the stages of preparation and data analysis. The purpose of this study is to apply the promethee method and build a website-based scholarship acceptance decision support system. This decision support system is designed using the PHP programming language and MySQL database. The type of research used is applied research, while the author's research method uses quantitative methods. The application of this decision support system is expected to facilitate the Study Program in the best decision-making process on receiving scholarships at the Fores University Information Systems Study Program.